Radiotherapy Adverse Effects Management Training for Health Workers in Andalas University Hospital - Rhandyka Rafli; Dian Ayu Hamama Pitra; Dita Hasni; Debie Anggraini; Seres Triola; Haves Ashan; Laura Zefira (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2022)
ABSTRACT Cancer services in Indonesia have experienced a rapid increase with the addition of radiotherapy facilities in various hospitals. Increasing radiotherapy facilities will also increase the incidence of adverse radiation effects. Based on the initial survey, it was found that health workers from various professions, including doctors, nurses, and radiographers, did not understand radiotherapy and the side effects that could occur to patients. Training aims: To increase the knowledge of health workers and skills in managing adverse effects according to the competence of each profession. Pre-training survey was used to find the knowledge and skills discrepancy. Online training is provided with knowledge transfer, followed by monitoring practice in the field. It was found that the understanding and skills of health workers regarding the adverse effects of radiation increased, Based on the results of the pre-test, post-test, and practice evaluation of 37 training participants. It is hoped that from this training, the quality of cancer services will be better and can improve the quality of life of patients undergoing radiotherapy treatment Keywords: Radiotherapy, Adverse Effects, Health Workers